Simulation model to estimate emotions in collaborative networks - Ferrada, Filipa (2020)
This work has been funded in part by the Center of Technology and Systems and the Portuguese FCT-PEST program UID/EEA/00066/2019 (Impactor project), and partly by the GloNet project funded by the European Commission.